Prevalence of atrial fibrillation in the general population and in high-risk groups: The ECHOES study - Davis, R; Hobbs, R; Kenkre, J; Roalfe, A; Iles, R; Lip, G; Davies, M (2012)
AimsTo establish the prevalence of atrial fibrillation (AF) in the general population in the UK, and in those with risk factors.Methods and resultsThe prevalence of AF on electrocardiography was established in prospectively selected groups: 3960 randomly selected from the population, aged 45; 782 with a previous diagnosis of heart failure; and 1062 with a record of myocardial infarction, hypertension, angina, or diabetes. Patients were also assessed clinically and with echocardiography. Mortality was tracked for 8 years. Atrial fibrillation was found in 78 of the random population sample (2.0). Prevalence was 1.6 in women and 2.4 in men, rising with age from 0.2 in those aged 45-54 to 8.0 in those aged 75 and older. Half of all cases were in patients aged 75 and older. Only 23 of the 78 (29.5) of those in AF took warfarin. Of the 782 patients, 175 (22.4) with a diagnosis of heart failure were in AF, with normal left ventricular function in 95 (54.3) of these. Atrial fibrillation was found in 14 of the 244 (5.7) of those with a history of myocardial infarction, 15 of the 388 (3.9) of those with hypertension, 15 of the 321 (4.7) of those with angina, and 11 of the 208 (5.3) of diabetics. Adjusting for age and sex, mortality was 1.57 times higher for those in AF.ConclusionAtrial fibrillation is common in the elderly and those with clinical risk factors. Screening these groups would identify many with AF. Use of anticoagulation was low at the time of the initial assessments in the late 1990s; practice may have changed recently. © 2012 Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2012. For permissions please email: journals.permissionsoup.com.